Assessment of Utility of Fine Needle Aspiration Cytology in Patients of Peripheral Lymphadenopathy- Experience of A Tertiary Care Hospital - Sharma, Upender; Singh, Ajit; Kamra, Hemlata T; Beniwal, Atul; Sharma, Sonam (Annals of Pathology and Laboratory Medicine, 2021)
Background: Fine needle aspiration cytology (FNAC) is a quick, sensitive, safe, reliable and cost-effective outdoor procedure that has a lower risk of complications as compared to a surgical biopsy. This study was conducted to analyse the various cytomorphological patterns establishing the diagnosis on FNAC in peripheral lymphadenopathy patients along with their clinical presentation. Methods: This study included 300 patients of peripheral lymphadenopathy in a tertiary care hospital of north-central Haryana. FNAC was done under all aseptic conditions and various cytomorphological patterns were analysed. Result: On stratification of lymph node lesions, 240/300 cases (80%) were reported as non-neoplastic and 60/300 cases (20%) as neoplastic lesions. Among the non-neoplastic lesions, granulomatous pathology was the commonest lesion encountered in 137/240 cases (57.1%), followed by reactive lymphoid hyperplasia and suppurative lymphadenitis. Metastatic involvement of lymph node was the commonest pathological finding diagnosed in 52/60 of malignant neoplastic cases (86.66%). Overall, the cervical lymph nodes were most commonly involved in 68.66% patients, followed by other lymph nodes. Conclusion: Lymphadenopathy can have varied etiologies ranging from non-neoplastic to neoplastic conditions. FNAC as a first line investigative procedure in lymphadenopathy patients obviates the need for surgical excision and guides subsequent patient therapy and management. The cervical group of lymph nodes are most commonly involved in both non neoplastic as well as neoplastic lymph node lesions. In younger age group (<30 years) non neoplastic causes of lymphadenopathy are more common whereas in elderly the malignant neoplastic causes are more common. The secondary metastatic carcinoma is more common than primary lymphoma of the lymph nodes.